The synergism of SMC1A cohesin gene silencing and bevacizumab against colorectal cancer - Maddalena Di Nardo; Simonetta Astigiano; Silvia Baldari; Maria Michela Pallotta; Giovanni Porta; Simona Pigozzi; Annalisa Antonini; Laura Emionite; Annalisa Frattini; Roberto Valli; Gabriele Toietta; Silvia Soddu; et al. (Journal of Experimental & Clinical Cancer Research, 2024)
Abstract Background SMC1A is a subunit of the cohesin complex that participates in many DNA- and chromosome-related biological processes. Previous studies have established that SMC1A is involved in cancer development and in particular, is overexpressed in chromosomally unstable human colorectal cancer (CRC). This study aimed to investigate whether SMC1A could serve as a therapeutic target for CRC. Methods At first, we studied the effects of either SMC1A overexpression or knockdown in vitro. Next, the outcome of SMC1A knocking down (alone or in combination with bevacizumab, a monoclonal antibody against vascular endothelial growth factor) was analyzed in vivo. Results We found that SMC1A knockdown affects cell proliferation and reduces the ability to grow in anchorage-independent manner. Next, we demonstrated that the silencing of SMC1A and the combo treatment were effective in increasing overall survival in a xenograft mouse model. Functional analyses indicated that both treatments lead to atypical mitotic figures and gene expression dysregulation. Differentially expressed genes were implicated in several pathways including gene transcription regulation, cellular proliferation, and other transformation-associated processes. Conclusions These results indicate that SMC1A silencing, in combination with bevacizumab, can represent a promising therapeutic strategy for human CRC.